A172 THE ASSOCIATION OF EFFICACY, OPTIMISM, UNCERTAINTY AND HEALTH ANXIETY IN INFLAMMATORY BOWEL DISEASE ACTIVITY OVER TIME. (4th March 2021) - Stone, J; Shafer, L; Graff, L A; Witges, K; Lix, L; Haviva, C; Targownik, L E; Bernstein, C N
Abstract: Aims: We aimed to assess if the presence of positive or negative psychological attributes are associated with disease activity in a prospective inflammatory bowel disease (IBD) cohort using validated psychological assessment tools and various measures of disease activity. Methods: The study included 146 adults with confirmed and recently active IBD enrolled in a prospective longitudinal cohort study. Demographics, disease information, validated measures of psychological functioning related to self-efficacy, optimism, health anxiety and intolerance of uncertainty were collected at baseline, week 26 and week 52. Disease activity indicators included fecal calprotection (FCAL), the Inflammatory Bowel Disease Symptom Inventory (IBDSI), and self-reported flares and were collected at study baseline, week 26 and week 52. Logistic regression was used to identify the relationship between psychological functioning and disease activity. Results: Participants' mean age was 42.9 years (SD 12.6; range 18–70), with 70.5% women. Almost two thirds (65.1%) had a diagnosis of Crohn's disease (CD), 34.2% had ulcerative colitis (UC), and 0.7% (n=1) was IBD unclassified. 22% had income <$50, 000 and 63% were in a current relationship. Patient-reported active disease (i.e., IBDSI; flare self-report) was significantly less likely with higher self-efficacy [OR= 0.87, 95% CI 0.82–0.93 (IBDSI); OR= 0.86, 95% CI 0.81–0.91 (self-report)] and significantly more likely with higher health anxiety (OR=1.09, 95% CI 1.04–1.15) with the association remaining for self-reported flares after adjusting for demographic variables. The psychological attributes were not associated with active disease based on FCAL levels. Conclusions: Higher health anxiety increases the likelihood of experiencing an IBD flare, while higher general self-efficacy may be protective of a disease flare. Funding Agencies: None